RQA integrated with ADI: Empowering biology students’ ability in posing higher-order thinking skills questions - Astuti Muh Amin; Duran Corebima Aloysius; Siti Zubaidah; Susriyati Mahanal (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Questions serve as an element that can be used to access and stimulate students’ thinking ability. This research aimed at analyzing the students’ ability to pose Higher-Order Thinking Skills (HOTS) questions during the learning process. This research was a survey research using a descriptive quantitative approach. The samples used in the research were biology education students of UIN Alauddin Makassar and Universitas Muslim Maros, South Sulawesi with the total of 92 students. The instrument used in this research was an observation sheet of questioning skills for the biology pre-service teachers. The results of this research showed that the implementations of RQA, ADI, and RQA integrated with ADI learning strategies were dominated with HOTS questions, while the learning using the conventional learning strategy was dominated with the Lower-Order Thinking Skills (LOTS) questions. The percentages of the HOTS questions in the learning using RQA, ADI, RQA integrated with ADI, and the conventional learning strategy were 60.53%, 55.71%, 64.91%, and 19.35% respectively.  This finding indicates that the RQA integrated with ADI strategy contributes the significant impact in stimulating students’ ability in posing HOTS questions in the classroom.